A PERANAN INKUBASI BISNIS DAN EKONOMI KELEMBAGAAN PADA PROSES PEMBENTUKAN KOPERASI WANITA PERTAMA DI PROVINSI DKI JAKARTA - Chandra, Dicky; Akbari, Deni Adha (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2020)
PKH encourages KM to have access to basic social services of health, education, food and nutrition, and other protection programs. However, the results of this program are still far from expected. The Ministry of Social Affairs through the collaboration between the Central Jakarta Social Service Office and the Muhammadiyah Prof. Dr. HAMKA University has started its first step with the theme "Counseling Family Development" and delivered the material "Financial Governance for Beneficiary Families (KPM) of the Family Hope Program (PKH) Senen District". The author gets a fact that turns out to be different. Of the 899 KPM invited, only 47 KPM attended. Most of them admitted that the social assistance funds received were used for consumptive purposes (not in accordance with the designation set by the Government Program). The PKH Facilitator of Senen District responded to the author's idea and asked the author and the FEB UHAMKA team to initiate the birth of the first or pioneer Consumer Cooperative in the DKI Jakarta area named "Koperasi TAMARA (Koperasi Wanita Mandiri Sejahtera)" and conduct regular guidance on the Cooperative, where all elements involved in it are women